The Developing Regorafenib Eye drops for neovascular Age-related Macular degeneration (DREAM) study: an open-label phase II trial - Joussen, Antonia M.; Wolf, Sebastian; Kaiser, Peter K.; Boyer, David; Schmelter, Thomas; Sandbrink, Rupert; Zeitz, Oliver; Deeg, Gesa; Richter, Annett; Zimmermann, Torsten; Hoechel, Joachim; Buetehorn, Ulf; et al. (British Journal of Clinical Pharmacology, 2019)
Aims This programme investigated topical regorafenib, a multikinase inhibitor, in patients with neovascular age-related macular degeneration (nAMD). Methods Topical regorafenib was investigated in an open-label, phase IIa/b study in which patients with choroidal neovascularization (CNV) secondary to nAMD received regorafenib (25 mu l, 30 mg ml(-1)) three times a day for 12 weeks. The primary endpoint of the phase II/a/b study was mean change in best-corrected visual acuity (BCVA) from baseline to weeks 4 and 12. Results In nAMD patients (N = 51), mean changes in BCVA were +1.2 [90% confidence interval (CI) -0.61, 2.97] and -2.4 (90% CI -4.18, -0.54) letters at weeks 4 and 12, respectively. Ocular treatment-emergent adverse events (TEAEs) (study eye) were reported in 21 patients by week 12. There was one serious ocular TEAE (visual acuity reduced) that was not drug related. Twenty patients required rescue (intravitreal ranibizumab). Conclusions The programme was terminated after phase IIa ended because efficacy was lower than with current nAMD treatments. According to elaborate post hoc analyses, the most likely reason was insufficient exposure in the target compartment (back of the eye).
CRIS-Team WoS Importer:2019-02-21